Models to estimate Brazilian indirect tensile strength of limestone in saturated state (Rudarsko-geološko-naftni zbornik, 2016)
There are a number of methods for estimating physical and mechanical characteristics. Principally, the most widely used method is regression, but recently,more sophisticated methods such as neural networks have frequently been applied as well. This paper presents the models of a simple and a multiple regression and neural networks –types Radial Basis Functionand Multiple Layer Perceptron, which can be used for the estimate of the Brazilian indirect tensile strength in saturated conditions. The paper includes the issues of collecting data for the analysis and modelling and an overview of the performed analysis with an efficacy assessment of the estimate foreach model. After the assessment, the model which provided the best estimate was selected, including the model which could have the most wide-spread application in the engineering practice.